(3TQM eWGdY GdCfhGQs - (3GdSQGL GdGQehj , eMehO Hf CHj HcQ Hf CMeO, SQGL GdOjf CHh GdKfGA,J (B682 (3g` s ((3YHOGdQMef Hf eMeO Hf CMeO GdYWGQi s)
(3BNQgG (B:s
(3hgh MO Gdcd GKfGA GdcdGe Ydi GdJYQja HGdeKGd s
(3GdehLhO TQM bSe GdefWbs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdadSaI hGdefWbs